Assessing trade dispute resolution mechanisms and the potential of an international trade tribunal in South Africa - Masamba, Magalie (University of Pretoria, 2021)
Mini Dissertation--(LLM (International Trade and Investment Law in Africa))- University of Pretoria, 2021.